Venom gland transcriptome analyses of two freshwater stingrays (Myliobatiformes: Potamotrygonidae) from Brazil - Júnior, Nelson Gomes De Oliveira; Fernandes, Gabriel Da Rocha; Cardoso, Marlon Henrique; Costa, Fabrício F.; Cândido, Elizabete De Souza; Neto, Domingos Garrone [UNESP]; Mortari, Márcia Renata; Schwartz, Elisabeth Ferroni; Franco, Octávio Luiz; De Alencar, Sérgio Amorim (Springer Nature, 2016)
Stingrays commonly cause human envenoming related accidents in populations of the sea, near rivers and lakes. Transcriptomic profiles have been used to elucidate components of animal venom, since they are capable of providing molecular information on the biology of the animal and could have biomedical applications. In this study, we elucidated the transcriptomic profile of the venom glands from two different freshwater stingray species that are endemic to the Paraná-Paraguay basin in Brazil, Potamotrygon amandae and Potamotrygon falkneri. Using RNA-Seq, we identified species-specific transcripts and overlapping proteins in the venom gland of both species. Among the transcripts related with envenoming, high abundance of hyaluronidases was observed in both species. In addition, we built three-dimensional homology models based on several venom transcripts identified. Our study represents a significant improvement in the information about the venoms employed by these two species and their molecular characteristics. Moreover, the information generated by our group helps in a better understanding of the biology of freshwater cartilaginous fishes and offers clues for the development of clinical treatments for stingray envenoming in Brazil and around the world. Finally, our results might have biomedical implications in developing treatments for complex diseases.